Syntheses of 1,2-amino alcohols and their applications for oxazaborolidine catalyzed enantioselective reduction of aromatic ketones - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S. (Australian Journal of Chemistry, 2007)
Six new chiral 1,2-amino alcohol derivatives have been synthesized starting from (1R, 2R)-2-amino-1-phenylpropane-1,3- diol. Asymmetric reduction of aryl ketones with in-situ generated oxazaborolidine from these amino alcohol derivatives and BH3 center dot Me2S afforded secondary alcohols with good yield and moderate to high enantiomeric excess.

Synthesis and antimicrobial activity of beta-lactam-bile acid conjugates linked via triazole - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Chavan, Pradnya S.; Deshpande, Mukund V. (Bioorganic & Medicinal Chemistry Letters, 2008)
Synthesis of novel 1,2,3-triazole-linked beta-lactam-bile acid conjugates 17-24 using 1,3-dipolar cycloaddition reaction of azido beta-lactam and terminal alkyne of bile acids in the presence of Cu( I) catalyst ( click chemistry) have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and moderate antibacterial activity against all the tested strains. (c) 2008 Elsevier Ltd. All rights reserved.

Synthesis and biological evaluation of bile acid dimers linked with 1,2,3-triazole and bis-beta-lactam - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit; Gonnade, Rajesh G. (Organic & Biomolecular Chemistry, 2008)
We report herein the synthesis and biological evaluation of bile acid dimers 11-18 linked through 1,2,3-triazole and bis-beta-lactam. The dimers 11-18 were synthesized using 1,3-dipolar cycloaddition reaction of diazido bis-beta-lactams 3, 4 and terminal alkynes 7-10 derived from cholic acid/deoxycholic acid in the presence of Cu(I) catalyst (click chemistry). These novel molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal as well as antibacterial activity against all the tested fungal and bacterial strains. Moreover, their in vitro cytotoxicities towards HEK-293 and MCF-7 cells were also established.